Formation of the Majiayao gold deposit, Jiaodong Peninsula, eastern China: Constraints from fluid inclusions, H–O–S–Pb isotopes, and pyrite Rb–Sr age. (12th December 2019) - Tian, Jiepeng; Li, Junjian; Zhang, Pengpeng; Li, Xiuzhang; Liu, Wengang; Tang, Wenlong; Fu, Chao; Dang, Zhicai; He, Jiangtao
Abstract : The Majiayao gold deposit at Qixia in Shandong Province is a typical gold deposit of medium–low temperature hydrothermal veins. This gold deposit is one of the most important types in the Jiaodong Peninsula. Four stages have been identified based on the cross‐cutting relationships and mineralogical and textural characteristics. The study of quartz vein fluid inclusions show that the inclusions can be divided into three categories: pure liquid or pure gas phase inclusions (type S), two‐phase gas and liquid inclusions (type W), and three‐phase inclusions rich in CO2 (type C). The results of laser Raman probe analysis show that the fluid inclusions are generally rich in CO2, thus forming a typical CO2 –H2 O–NaCl system. The fluid temperature results show that in stage I, only the type W fluid inclusions are identified by microthermometry, the homogenized temperatures (to liquid) are 210–343°C and mostly range from 260 to 280°C, the range of salinity is 1.57–10.98 wt.% NaCl, with a peak value of 8–11 wt.% NaCl, and the density is 0.65–1.02 g/cm 3, with a peak value of 0.81–0.87 g/cm 3 ; in stages II and III, the primary fluid inclusion assemblages include both type W and C inclusions, which show similar phase‐transition temperatures and are trapped between 190 and 300°C, and the peak values of salinities are 4–10 wt.% NaCl equivalent; and in stage IV, the total homogenization temperatures (Th‐TOT ) into liquid range from 120 to 220°C, and the range of salinities is 4.2–7.9 wt.% NaCl. These values indicate that temperature, salinity, and density gradually decreased from the early to late mineralization stage. The ore‐forming fluid of the deposit was a thermal liquid system with medium–low temperature, medium–low salinity, and low density and was rich in reducing CO2 . The H–O isotope shows that the ore‐forming fluids were dominated by metamorphic fluid with only minor amounts of meteoric water involved in the ore‐forming process. According to the S, Pb, and Sr isotopes analysis, it indicated that the source of ore‐forming materials is mainly crustal fluid. The measured Rb–Sr isochron age of pyrite is 123.4 ± 2.9 Ma, which indicates that the metallogenic age corresponded to the Early Cretaceous.